Children in time and place : (Cambridge University Press, 1993)
Children in Time and Place begins with studies that link historical life transitions in children's lives with emphasis on wartime experience. It turns to studies of historical variation in the effect of life transitions, from the onset of sexual experience to the transition to fatherhood, and it concludes by introducing the reader to the collaborative efforts involved in the workshop that led to the volume. This book will be of interest to developmental psychologists, sociologists, and historians.